The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.devcel.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolving CENP-A and CAL1 Domains Mediate Centromeric CENP-A Deposition across Drosophila Species

Abstract: SUMMARY Centromeres mediate the conserved process of chromosome segregation, yet centromeric DNA and the centromeric histone, CENP-A, are rapidly evolving. The rapid evolution of Drosophila CENP-A loop 1 (L1) is thought to modulate the DNA-binding preferences of CENP-A to counteract centromere drive, the preferential transmission of chromosomes with expanded centromeric satellites. Consistent with this model, CENP-A from Drosophila bipectinata (bip) cannot localize to Drosophila melanogaster (mel) centromeres.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 61 publications
2
55
0
Order By: Relevance
“…Alternatively, other centromere-associated protein(s) may provide DNA-sequence specificity and evolve to suppress centromere drive Malik and Henikoff 2009). Adaptive evolution of CENH3 could in turn be driven by its interaction with these proteins, for example CENP-C, or instead be driven by modulation of its centromere deposition efficiency through its loading factor as proposed for Drosophila (Rosin and Mellone 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, other centromere-associated protein(s) may provide DNA-sequence specificity and evolve to suppress centromere drive Malik and Henikoff 2009). Adaptive evolution of CENH3 could in turn be driven by its interaction with these proteins, for example CENP-C, or instead be driven by modulation of its centromere deposition efficiency through its loading factor as proposed for Drosophila (Rosin and Mellone 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Functional orthologs with limited sequence similarity to HJURP exist in S. cerevisiae , S. pombe , and D. melanogaster (named Scm3 and Cal1) [369,370,371,372,373,374,375,376,377,378,379]. HJURP, which may form functional dimers [380], contains an N-terminal Scm3-homology domain that binds pre-nucleosomal CENP-A [73,75,158,381,382,383,384].…”
Section: The Propagation Of Centromeric Chromatinmentioning
confidence: 99%
“…Importantly, in either situation (Figure 3BI–II), modulating CENP-A binding could also be accomplished by CENP-A alleles that somehow alter CENP-A’s deposition by its chaperone [113], as discussed below.…”
Section: Models Of How Cenp-a Could Suppress Centromere Drivementioning
confidence: 99%
“…This work showed that the presence of an evolutionarily compatible CAL1 partner is the only requirement for centromeric targeting, even across large evolutionary distances where the centromeric DNA sequences have presumably diverged (Figure 4A; [113]).…”
Section: The Presence Of Species-matched Cenp-a and Cal1 Allows Cenp-mentioning
confidence: 99%